2021
DOI: 10.2176/nmccrj.cr.2021-0089
|View full text |Cite
|
Sign up to set email alerts
|

Acute Thrombectomy for Contralateral Internal Carotid Artery Occlusion after Revascularization Surgery for Quasi-moyamoya Disease: A Case Report

Abstract: Ischemic complications can occur after revascularization surgery for moyamoya disease, but acute contralateral internal carotid artery (ICA) occlusion is an extremely rare complication. The patient was a 51-year-old woman with no medical history. Left frontal lobe infarction and bilateral ICA terminal stenosis were identified by repeated transient right paresis and aphasia. We diagnosed her with quasi-moyamoya disease associated with hyperthyroidism and performed revascularization surgery for the symptomatic l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…A few reports showed low survival in patients hospitalized in coma [6,18,19]. However, several recent reports have shown that endovascular reperfusion as a first stage can improve the prognosis, especially if the time from symptom onset is less than 5 h [20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…A few reports showed low survival in patients hospitalized in coma [6,18,19]. However, several recent reports have shown that endovascular reperfusion as a first stage can improve the prognosis, especially if the time from symptom onset is less than 5 h [20][21][22].…”
Section: Discussionmentioning
confidence: 99%